Factors that affect employee’s awareness toward unit trust in Putra Specialist Hospital (Melaka) Sdn Bhd - Zakaria, Aimie Suhaili (2012)
This study project was conducted to identify the level on employee’s awareness toward Unit Trust in Putra Specialist Hospital (Melaka) Sdn Bhd. The purpose of this study is to determine the relationship between the public awareness with performance, information and cost-benefit in the financial issue. Hence, this study also determines the elements that can be used to improve the level of awareness for unit trust. The researcher adapts the literature review from the past researcher that are related to the area of this study. Furthermore, the research methodology then, helps the researcher to generate the findings from the distributed questionnaire. The data analysis such as Reliability Statistic (Cronbach’s alpha), Frequencies (demographic statistic), Descriptive statistic and Correlation helps to interpret the data successfully. Then, the conclusion and recommendation will come out.